Legal Regulation of Electronic Money Turnover: Global Trends - Raiymbergenova, Kamshat T.; Aigarinova, Gulnar T.; Atakhanova, Saltanat K.; Saparov, Bakhytzhan Zh.; Nakisheva, Makhabbat K. (Law, State and Telecommunications Review, 2023)
[Purpose] To analyse the existing trends in the turnover of electronic money, and their relationship with the conventional cash turnover on the territory of the Eurasian Economic Union (EEU), in particular, in the legal system of the Republic of Kazakhstan (RK). [Methodology/Approach/Design] Deduction, content analysis, comparative analysis, and other general and special research methods were used. [Findings] As a result, the existing problems in the functioning of the type of money considered in this study were analysed. The study includes recommended measures to introduce amendments to legislation aimed at removing barriers to the functioning and circulation of electronic money, which will benefit the economic system of the given state. [Practical Implications] The information presented in this article can be useful material for representatives of public authorities in the implementation of reforms to modernise the economic system, for a wide range of readers interested in the development of digital technologies and their impact on the commercial activities of subjects of the economic life of society.